2020
DOI: 10.1101/2020.03.24.20042606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modes of contact and risk of transmission in COVID-19 among close contacts

Abstract: doctoral student, Pei-liang Chen 2 , master's 8 students, Hua-min Liu 2 , doctoral student, Xin Cheng 2 , master's students, 9 Miao-chun Cai 2 , master's students, Qing-mei Huang 2 , master's students, 1 0

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
151
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 25 publications
7
151
0
8
Order By: Relevance
“…9-13 Figure 1. Screening and selection of articles Their sampling frames were residential aged care facilities (RACF) in USA 12,13 ; a community sample of source cases and their close contacts 11 ; a community screening program of Shenzhen cases and their close contacts including hospitalized patients, fever clinics and travelers contacts 10 and a whole District surveillance program in Italy 9 . The demographic characteristics (Table 1) indicate that most of the tested individuals were adults, with mean age over 70 years in the two RACF studies, 12,13 and mean over 37 years in the three 9-11 community screening programs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9-13 Figure 1. Screening and selection of articles Their sampling frames were residential aged care facilities (RACF) in USA 12,13 ; a community sample of source cases and their close contacts 11 ; a community screening program of Shenzhen cases and their close contacts including hospitalized patients, fever clinics and travelers contacts 10 and a whole District surveillance program in Italy 9 . The demographic characteristics (Table 1) indicate that most of the tested individuals were adults, with mean age over 70 years in the two RACF studies, 12,13 and mean over 37 years in the three 9-11 community screening programs.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 1) Diagnosis in all studies was confirmed via RT-qPCR and in one case supplemented with radiological evidence. 11 Testing intensity varied across settings and in the eligible studies intensity was generally over 85% as follows: all contacts regardless of symptoms; 10-12 93% of residents 13 and 85.9% of an entire town. 9 The case definitions for asymptomatic cases usually included self-reported absence of fever and cough 10,12 in addition to absence of other symptoms, 9 self-report supplemented with chart abstraction in the RACFs for people with severe cognitive impairment, 12,13 or described as "asymptomatic throughout" the study period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al [1] similarly considered 167 infected patients of whom 5 (3%) tested negative by RT-PCR at initial presentation. Fang et al [3] found that RT-PCR was only able to identify 36/51 (71%) of SARS-CoV-2 infected patients when using swabs taken 0-6 days after the onset of symptoms, and Luo et al [9] similarly reported that the initial sensitivity of throat swabs in secondary contacts was 71%.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the discretised distribution of time to confirmation among symptomatic individuals from[9] and the distribution of time to test that we estimate, combining this with our estimate of the false-negative test probability from nasal swabs, assuming false-positive tests are impossible (see Supplementary Methods).…”
mentioning
confidence: 99%